Recognition and specific degradation of bacteriophage T4 mRNAs. - Ueno, H (2001)
Gene 61.5 of bacteriophage T4 has a unique role in gene expression. When this gene is mutated, mRNAs of many late genes are rapidly degraded, resulting in late-gene silencing. Here, we characterize an extragenic suppressor, ssf5, of a gene 61.5 mutation. ssf5 was found to be an amber mutation in motA, which encodes a transcription activator for T4 middle genes. When this gene is mutated, both degradation and specific cleavage of late-gene mRNA is induced after a delay, as exemplified by soc mRNA. Consequently, partial late-gene expression occurs. In an ssf5 genetic background, a gene 61.5 mutation exhibits a novel phenotype: in contrast to late-gene mRNA, middle-gene mRNA is stabilized and the expression of middle genes is prolonged. This is attributable to an activity of gene 61.5 specific for degradation of middle-gene mRNA. The degradation of middle-gene mRNA in the presence of a normal gene 61.5 appears in parallel with the degradation of late-gene mRNA in its absence. This observation suggests that the mRNA-degrading activity that silences late genes in cells infected with a gene 61.5 mutant is targeted to middle-gene mRNA when gene 61.5 is wild type. These results and the results obtained in the presence of a normal motA gene suggest that gene 61.5 protein functions to discriminate mRNAs for degradation in a stage-dependent manner.